Generating indicators of appropriate feeding of children 6 through 23 months from the KPC 2000+ - Arimond, Mary; Ruel, Marie T. (Academy for Educational Development, 2003)
Nutrition interventions designed to improve complementary feeding practices are one component of many child survival and health programs. Program planners and managers need indicators of adequate or optimal complementary feeding for a variety of purposes. For example, indicators are needed to establish the baseline prevalence of key feeding practices and to assess progress towards objectives. In USAID-funded Child Survival and Health projects, Knowledge, Practices and Coverage (KPC) surveys are used as a tool for gathering quantitative information on a range of practices, including complementary feeding practices. The KPC survey tool also includes a set of tabulation guidelines for recommended indicators. The current KPC questionnaire (KPC 2000+) includes a set of questions about complementary feeding. Respondents are asked about foods and liquids given to the sample child the previous day, and about frequency of feeding....In addition to providing a set of indicators, this document includes resources for generating useful descriptive information using the KPC. Definitions and justifications for the suggested indicators are followed by recommendations for minor changes to the KPC questionnaire. The KPC questionnaire is meant to be adapted to local circumstances and priorities. To facilitate this, we provide recommendations for topics to be covered in pre-survey qualitative work, which will generate information needed both for program planning, and for appropriately adapting the complementary feeding questions on the questionnaire. The last section provides suggestions for descriptive presentations of infant and young child feeding survey results." -- from Executive Summary.